1992
DOI: 10.1002/ijc.2910510613
|View full text |Cite
|
Sign up to set email alerts
|

In vitro activity of novel antifolates against human squamous carcinoma cell lines of the head and neck with inherent resistance to methotrexate

Abstract: A series of 7 human squamous carcinoma cell lines of the head and neck (HNSCC), grown in standard medium containing high folate concentrations and in "folate-conditioned" medium containing nanomolar concentrations of folates, were all found to be sensitive (IC50: less than or equal to 50 nM) in growth-inhibition studies to methotrexate (MTX) following drug exposure for 7 days. However, when MTX exposure was limited to 24 hr, only 2 out of 7 HNSCC cell lines were sensitive to MTX (IC50: less than 500 nM), 2 wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

1993
1993
2009
2009

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 16 publications
2
8
0
Order By: Relevance
“… FPGS activity in HF and LF colon cancer and HNSCC cell lines. Extracts of colon cancer and HNSCC cell lines (Van der Laan et al ., 1992) were used for the determination of the FPGS activity with 250 μM MTX as a substrate. The FPGS activity was expressed as pmol 3 H‐glutamate incorporated/hr/mg protein.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… FPGS activity in HF and LF colon cancer and HNSCC cell lines. Extracts of colon cancer and HNSCC cell lines (Van der Laan et al ., 1992) were used for the determination of the FPGS activity with 250 μM MTX as a substrate. The FPGS activity was expressed as pmol 3 H‐glutamate incorporated/hr/mg protein.…”
Section: Resultsmentioning
confidence: 99%
“…The HNSCC cell lines were cultured in “standard folate” RPMI 1640 medium (containing 2.2 μM folic acid) and supplemented with 10% FCS. Each of the 7 cell lines described above were adapted in a period of 5–6 months to grow at low folate conditions (WiDr/F, C26‐10/F, C26‐A/F, C26‐G/F and 11B/F, 14C/F and 22B/F) (Van der Wilt et al ., 1995; Van der Laan et al ., 1992) and cultured in folate‐free RPMI 1640 supplemented with 10% dialyzed FCS, 2 mM glutamine and 2.5 nM LV (for the murine colon cancer cells), 1.0 nM LV (for WiDr/F) and 0.5 nM LV (for the HNSCC cells). The cell lines cultured in “standard folate” medium will be further referred to as HF (high folate) cells, whereas cells grown under low folate conditions will be referred to as LF (low folate) cells.…”
Section: Methodsmentioning
confidence: 99%
“…23,24), and WiDr (colon; ref. 25) were either grown in standard RPMI 1640 (Cambrex BioScience) containing 2.3 Amol/L supraphysiologic folic acid (HF) supplemented with 10% FCS (Greiner Bio-One) and 20 mmol/L HEPES (Cambrex BioScience) or adapted to more physiologic concentrations of folates (1-5 nmol/L folic acid or leucovorin; LF) by gradually decreasing the folate concentrations in the medium over a period of up to 4 months, depending on the cell line, followed by monitoring these cells under these conditions for at least 1 year.…”
Section: Chemicalsmentioning
confidence: 99%
“…Recent reports have shown that a number of human cell lines derived from solid tumors display increased sensitivity to antifolates and 5‐FU when grown in low folate medium (43,44). This is associated with reduced TS protein and activity levels as well as FdUMP binding sites (44).…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports have shown that a number of human cell lines derived from solid tumors display increased sensitivity to antifolates and 5‐FU when grown in low folate medium (43,44). This is associated with reduced TS protein and activity levels as well as FdUMP binding sites (44). These cells also increase their RFC activity from two‐ to seven‐fold, but do not alter their folylpolyglutamate synthetase (FPGS) levels even though in some cases they do show an accumulation of MTX triglutamates.…”
Section: Discussionmentioning
confidence: 99%